Adversity Quotient (AQ), Status Sosial Ekonomi dan Intensi Wirausaha Siswa - Cahyana Nursidiq (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This study is intended to determine the differences of students' entrepreneurial tendencies in terms of Adversity Quotient (AQ) and socio-economic background. The subjects in this study were 61 students of SMK Batik Purworejo. Samples were taken using a random sampling lottery system. The data collection method was use of an Adversity Quotient (AQ) questionnaire and an entrepreneurial tendencies questionnaire, while the data analysis used was an analysis of variance equipped with descriptive analysis. The results showed that there were differences in students' entrepreneurial tendencies in terms of Adversity Quotient (AQ): “climber” students tended to have high entrepreneurial tendencies, while “quitter” students had low entrepreneurial tendencies. In contrast to AQ, socioeconomic status has no effect on entrepreneurial tendency. Individuals with low, medium and high socioeconomic status all may have moderate entrepreneurial tendencies. When both measured together there is no difference in entrepreneurial tendency based on AQ and socioeconomic status